“For You Your Religion and For Me My Religion”: A Theological Limitation on Religious Inclusivism and Religious - Alniatul Fadilah; Ahmad Yusam Thobroni; Alvita Niamullah; Eka Pratiwi Wulandari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
The idea of ​​religious pluralism shows each group respecting and tolerant of each other and religious inclusivism which emphasizes that all religions have the same value of truth, is present as one of the resolutions to the problems of differences in religious views. However, it turns out that some implementations of these ideas actually seem to be forcing and going beyond the limits, such as a group of Muslims who play Marais and sing the Prophet’s prayers during the inauguration of a church or a priest who chants prayers during a church mass ceremony. This article aims to limit the implementation of the idea of ​​religious pluralism and religious inclusivism using the argument of Q.S. Al-Kafirun: 6 “For you your religion and for me my religion”. The data collection technique in this study uses a literature study excavated from interpretation books as primary sources and research articles and books as secondary sources so that it can be concluded into a type of descriptive-analytical-qualitative research. The results of the analysis show that Islam recognizes religious diversity as part of the sunnatullah, but does not justify actions that lead to syncretism which has the potential to blur religious identity. This study contributes to enriching the discourse of religious pluralism and religious inclusivism in Indonesia regarding the importance of maintaining a balance between respecting religious differences while maintaining the essence of the teachings of each perspective of the interpretation of the Qur’an.